Salmonella enterica Serovar Typhimurium and Enteritidis Isolated from Raw Shrimp in Bangladesh: An Investigation Based on Molecular Characteristics, Survival, Virulence, Antibiotic Resistance, and Biofilm Formation Attributes - Prosanto Kumar Das; Ananta Mandal; Md. Mizanur Rahman; Shovon Lal Sarkar; Iqbal Kabir Jahid; Md. Anwar Hossain; A. S. M. Rubayet Ul Alam; Pravas Chandra Roy (Journal of Food Quality)
Shrimp is the white gold of Bangladesh, with the second-highest income source from exporting to foreign countries. Contamination with Salmonella spp. is now one of the significant issues for Bangladesh to export. Proper characterization of the salmonella pathogen is thus necessary to avoid undesirable losses due to the rejection of exported shrimp. In Bangladesh, the present condition of raw shrimp contamination with pathogenic Salmonella serovars and their survival/virulence properties was not adequately characterized. In this study, we collected 43 raw shrimps as samples from different farms in Jashore, Khulna, and Sathkhira regions. We then maintained standard cultural and biochemical protocols for isolating Salmonella strains, followed by the molecular identification of particular Salmonella serovars. The standard method for checking its credibility to form biofilm in 0–10% NaCl, tolerate acid/bile stress likewise in the gastrointestinal tract, and resist antimicrobial pressure was performed individually with the particular pathogenic strains. Our results successfully identified eleven Salmonella strains with three typhimurium serovars and three enteritidis serovars, which have biofilm-forming capability up to 4–8% NaCl, acid/bile habituation alike stomach/small intestine of humans, and resistance against necessary antibiotics generally used in treating human and poultry infection signifying the impending danger in the shrimp industry. While previous studies of Bangladesh successfully isolated Salmonella only presumptively, our research focused mainly on molecular characterization of the human Salmonella pathogen along with important survival and virulent attributes, such as biofilm formation, acid/bile tolerance, and antibiotic resistance of selected S. typhimurium and S. enteritidis strains. Further study with more sampling will be necessary to confer the transmission route of the pathogen from the natural reservoir to the shrimp industry.